The method of targeted delivery of drugs to the posterior segment of the eye - A.E. Egorov; D.V. Katz; Baeva N.G; A.B. Movsisyan (РМЖ "Клиническая офтальмология")
Egorov A.E.1,2, Kats D.V.1,2, Baeva N.G.1,2, Movsyasyan A.B. 1 1 Pirogov Russian National Research Medical University, Moscow 2 Municipal Clinical Hospital № 15 named after O.M. Filatov, Moscow Aim: to analyze the dynamics of patients’ visual functions with primary open-angle glaucoma (POAG) with preserved visual functions (PVF) and compensated intraocular pressure (IOP) after conducting trophic modified laser coagulation (tMLC). Patients and methods: the study included 67 patients (97 eyes) with moderate and advanced stages of open-angle glaucoma and normalized intraocular pressure. The examination for all patients included: anamnesis of disease, life, also a comprehensive ophthalmological examination was carried out, including visual acuity, tonometry, biomicroscopy, automated perimetry using kinetic visual field and central threshold test. In the study, patients were examined 4 times: before treatment, 5 days after tMLC, 1 month after tMLC and 5 month after tMLC. Trophic modified laser coagulation was performed in two stages: the creation of zones of increased permeability blood-ocular barrier (BOB) and the injection of the drug in that area. Results: patients with compensated POAG and PVF after conducting tMLC observed improvement of visual fields and patients noted subjective contrast enhancement of the image. Evaluation of average visual acuity data revealed an increase for 45.2% in a month after the treatment. The analysis of computer perimetry data revealed an extension of peripheral visual fields by 6.9% on average compared to the original ones. Conclusion: the research suggest the effectiveness, safety and prospective use tMLC as neuroretinoprotective therapy in patients with compensated POAG and PVF, it is provided that a stable and uniform reception of the drug to almost inaccessible structures of the posterior segment of the eye by overcoming blood-ocular barrier. Key words: primary open-angle glaucoma, optic neuropathy glaucoma, neuroretinoprotection, trophic modified coagulation. For citation: Egorov A.E., Kats D.V., Baeva N.G., Movsyasyan A.B. The method of targeted delivery of drugs to the posterior segment of the eye // RMJ “Clinical ophthalmology”. 2018;1:26–29.